Survey on Early Detection of Autism Using Data Mining Techniques - Ida Seraphim, B; Samuel Rao, Lavi; Joshi, Shiwani (International Journal of Engineering and Technology, 2018)
The children of today are the future of the nation and there are many hurdles in their development like ASD.ASD (Autism Spectrum Disorder) is a neurological disorder which has a lifetime impact on the basic skills and talents of a human being. The foremost goal of the paper is to know the number of people suffering from autism and the various symptoms of autism.Â Â Â Â